Intelectuales y revolución. Científicos sociales latinoamericanos en el MIR chileno (1965-1973) - Lozoya, Ivette (Ariadna Ediciones, 2020)
This book examines the ideas that are part of Latin American political, economic and philosophical thought that became a reference for the Chilean MIR. The relationship that existed between Latin American social scientists and the revolutionary organization is described and problematized, differentiating between those who played a role of reference and those who were militants of the MIR. For this, the intellectual networks that allowed the dissemination of thought at a general level in Latin America are analyzed, as well as the ties that the Mirista intellectuals had established with their Latin American similes